CONSUMER PREFERENCE TOWARDS PURCHASING IMPORTED APPLES AT TANJUNGSARI MARKET, SURABAYA - Nabila, Naufal Elvia; Hendrarini, Hamidah; Winarno, Sri Tjondro (Agridevina : Berkala Ilmiah Agribisnis, 2024)
Sales of imported apples in Indonesia have increased from year to year. This is due to the large number of traders selling imported apples at Tanjungsari Market, Surabaya. The problem that occurs at the Tanjungsari Surabaya Fruit Market is that there is a tendency for consumers to buy imported apples rather than local fruit. This research aims to analyze the attributes that consumers prefer for imported apples and find out the attributes that consumers most consider when purchasing imported apples. The sample determination method in the research used purposive sampling, with 60 respondents. This research's data analysis method uses Multiattribute Fishbein analysis to determine the attributes that consumers most consider when purchasing imported apples. As a result of the research that has been carried out, it can be seen that the attributes of imported apples are the preference of consumers at the Tanjungsari Market in Surabaya, namely they have a cheap price, sweet taste, large size, red color, with a strong aroma, the type of fruit chosen is apples. fuji, the freshness of the fruit has a hard skin, the ease of buying imported apples is very easy, and the texture of the flesh of imported apples is hard or crunchy and dense. Meanwhile, the attribute that is most considered when purchasing imported apples at the Tanjungsari Market in Surabaya is the freshness of the apples. Meanwhile, the order of attributes from the most considered to the least considered is freshness, price, taste, texture, color, ease of purchase, size, aroma and brand of imported apples.